Pemanfaatan Penginderaan Jauh Dalam Bidang Geologi - Mamonto, Ahmad Firly; Lahay, Muamart; Hermawan, Riki; Panai, Irdiansyah; Puhi, Riyan; Maryati, Sri; Akase, Noviar; Sune, Nawir (Universitas Negeri Gorontalo, 2025)
This study summarizes various studies on the use of remote sensing technology, both multispectral and radar, in the fields of geology, hydrology, and the environment. The main journals reviewed show that satellite imagery such as Landsat TM, Landsat 8 OLI/TIRS, Sentinel-2, ASTER, and LiDAR radar data play a significant role in identifying the physical characteristics of the earth, such as soil moisture, mineralization, lithology, suspended sediments, and surface deformation due to tectonic activity. The use of multispectral imagery is effective in mapping lithology and minerals, while radar and LiDAR remote sensing excel in morphological analysis, geological structure, and hydrodynamic modelling of flood inundation. Overall, remote sensing has proven to be an efficient, time-saving, and accurate tool in supporting geological resource exploration, topographic mapping, and natural disaster mitigation. The integration of various image data sources increases the validity of interpretation results and can be an important basis for decision-making related to spatial planning, mineral exploration, and environmental management in Indonesia.